Building Monetary and Financial Systems : Case Studies in Technical Assistance. (International Monetary Fund, 2007)
This book includes 21 case studies of technical assistance provided by the IMF's former Monetary and Financial Systems Department during 2003-06. These studies cover issues related to monetary policy and operations, financial markets, payment systems, and financial regulation and supervision, with an emphasis on both the substance of the issues and the modalities of technical support. The book illustrates that the formulation of sound monetary and financial policies needs to be complemented by proper and efficient implementation. It shows how weaknesses in institutional capacity can hinder policy implementation and how these weakenesses can be overcome to achieve a desirable level of monetary and financial stability. In addition to traditional elements of the official financial infrastructure, such as the capacity to conduct monetary and foreign exchange operations or effectively supervise banks and other financial institutions, the book also presents information on recent developments in governance arrangements.